Flavonoids from Impatiens grandulifera and Their Antioxidant Activity - A. K. Whaley; R. I. Lukashov; A. O. Whaley; E. V. Zhokhova; N. S. Gurina; M. U. Goncharov; G. P. Yakovlev; V. A. Tsiarletskaya (Разработка и регистрация лекарственных средств, 2023)
Introduction. The genus Impatiens L. includes about 850 species, which are found mainly in tropical and subtropical climate zones. The Indigenous people of Pakistan used pastes and extracts from I. glandulifera for the treatment of joint pain, anxiety and skin allergies [6]. Flowers of I. glandulifera are used in Bach flower remedies, which are used for sedation, relaxation and helping to balance emotional states.Aim. Isolation and structural elucidation of 11 phenolic constituents from the aerial parts of I. glandulifera and the evaluation of their antioxidant activity.Materials and methods. The aerial part of Impatiens glandulifera Royle was collected in the Leningrad region near the village of Orekhovo in 2021. Fractions were analyzed by analytical high performance liquid chromatography (HPLC) using a Prominence LC-20 (Shimadzu, Japan) equipped with a diode array detector. The isolation of individual compounds was carried out by column chromatography on open glass columns with sorbents of different selectivity, as well as by preparative HPLC using a Smartlina (Knauer, Germany) equipped with a spectrophotometric detector. The structure of isolated individual compounds was established by 1D and 2D NMR spectroscopy (Bruker Avance III 400 MHz, Germany). To study the antioxidant activity, we used solutions obtained by dissolving the isolated substances in a mixture of dimethyl sulfoxide and ethanol; an aqueous solution of vitamin C and an alcoholic solution of Trolox (Sigma-Aldrich, Japan).Result and discussion. Phytochemical analysis of the aerial parts of Impatiens glandulifera Royle. resulted in the isolation of 11 polyphenolic secondary metabolites (1-11) and their structures were elucidated. The antioxidant activity of all isolated compounds was evaluated.Conclusion. The maximum RAP values of eriodyctiol (3), kaempferol (1), and quercetin (2) did not differ significantly (p = 0.585) from those of the comparator preparations: vitamin C and Trolox, which indicates that the antioxidant effect of these three isolated compounds is comparable to the well-known antioxidants. However, the semi-effective concentrations of these substances are two or more times lower (p = 2.56 · 10–4) comparted with vitamin C.